Psycho-social study of adolescent girls of rural Konkan region (Maharashtra) - Pevekar, Krishna S.; Patil, Suvarna N.; Chavan, Ashwini J. (International Journal of Research in Medical Sciences, 2017)
Background: Konkan area in Maharashtra, India is rich in Biodiversity and known for its Natural Beauty. At the same time geographical difficulties, poor socio-economical status, superstitial and religious beliefs are some important factors contributing to more Psycho-social problems in this area including Physical Health. We focused in this Study to find out Psychological Problems, Health issues and planning future activities for School going adolescent girls. Methods: The Study was carried out on total no. Of 1290 School going adolescent girls of age group 11-20 years, over the period of six months. The following Psychological and Physical parameters were considered. Mental Status Examination, Higher Mental Functions, Personality, Decision Making capacity. Hemoglobin status, Body Mass Index and Health related factors of Adolescent girls. Results: According to Psychological assessment78.46% had abnormal expression, poor hygiene, low decision making. 72.47% were underweight and 47.22% were anemic. Conclusions: More Active measures need to be taken for care of Psychological and Physical health. Awareness Programme needs to implement for Students, Parents, Teachers and Public.